An Overview Of Current Status Of Cutting Fluids And Cooling Techniques Of Turning Hard Steel - Liew, Pay Jun; Shaaroni, Ainusyafiqah; Che Sidik, Nor Azwadi; Yan, Jiwang (ELSEVIER, 2017)
In the recent years, there has been increasing interest in hard turning over grinding for machining of hardened steels. There are some issues in the process which should be understood and dealt with such as friction and heat generation at the cutting area that can affect the tool life and surface finish apart from other machining results to achieve successful performance. Researchers have worked upon several aspects related to hard turning and came up with their own recommendations to overcome these problems. They have tried to investigate the effects of tool materials, cutting parameters, different cooling type and cooling technique on different machinability responses like tool life, surface roughness, cutting forces, chip morphology, etc. This paper presents a comprehensive literature review on cutting fluids and cooling technique on turning of hardened steels. Type of tools and cutting parameters used by the researchers have been summarized and presented in this paper as well to give proper attention to the various researcher works.